C:N:P stoichiometric variations of herbs and its relationships with soil properties and species relative abundance along the Xiaokai River irrigation in the Yellow River Delta, China - Jiang, Peipei; Han, Xiaojun; Liu, Ziyu; Fan, Shoujin; Zhang, Xuejie (Frontiers in Plant Science, 2023)
Soil salinity is known to affect plant performance and nutrient stoichiometry by altering their ecophysiology, and thus playing a crucial role in determining plant distribution patterns and nutrient cycles in salinized ecosystems. However, there was little consensus on the effects of salinity stress on plant C, N, and P stoichiometries. Moreover, determining the relationships between species relative species abundance and plant C, N, and P stoichiometries can help to understand the different adaptive strategies between the common and rare species as well as the community assembly process. Here, we determined the plant C, N, P stoichiometries at the community and species levels and the relative abundance of species as well as the corresponding soil properties from five sampling sites along a soil salinity gradient in the Yellow River Delta, China. We found that the C concentration of belowground part increased with soil salinity. Meanwhile, plant community N concentration and C:N ratio tended to decrease with soil salinity, whereas the P concentration, C:P, and N:P ratios exhibited the opposite trends. This indicated that N use efficiency increased, while P use efficiency decreased with soil salinity. Moreover, the decreased N:P ratio indicated that N limitation was gradually aggravated along the soil salinity gradient. The soil C:P ratio and P concentration were the major factors of plant C, N, and P stoichiometries in the early growth stage, whereas the soil pH and P concentration were the major factors of plant C, N, and P stoichiometries in the late growth stage. Compared with that of the rare species, the C:N:P stoichiometry of the most common species was medium. Moreover, the intraspecific variations in the aboveground part N:P ratio and belowground part C concentration showed a significant correlation with species’ relative abundance, which indicated that higher intraspecific trait variation might facilitate greater fitness and survival opportunities in environments with high heterogeneity. Our results revealed that the plant community C:N:P stoichiometry and its determining soil properties varied with plant tissues as well as sampling seasons, and emphasized the importance of intraspecific variation in determining the functional response of plant communities to salinity stress.